Fully Functional Recovery after Brainstem Infarction in a Young Patient- A Case Report - Huang, Pengyu; Lu, Dandan; Lu, Haixia (Archives of Clinical and Medical Case Reports, 2022)
Ischemic brainstem infarction is extremely rare in the young people under 30 years old but with severe symptoms and poor prognosis. It is commonly caused by stenosis and occlusion of the vertebrobasilar artery and its branch vessels. Here we reported a 26-year old male brainstem infarction patient with severe hemiplegia and dizziness on admission. He has no hypertension, obesity, diabetes and other chronic diseases, which are the most common reasons for infarction, but has a long history for smoking and drinking. Immediately after acute drug therapy for circulation improvement, he received personalized treatment with drug medication plus physical rehabilitation. The myodynamia, motor balance and living ability fully recovered 5 months later. This case leads us to call for more attention to brainstem infarction patient younger than 30 years in the hope for new strategies for both diagnosing and treatment.